Elaboración de un plan de marketing para el hostal Pamplona de la ciudad de Cariamanga, cantón Calvas, provincia de Loja - Álvarez Rosario, Yessenia Isabel (2017)
n the following investigative work, the topic of study was the "DEVELOPMENT OF A MARKETING PLAN FOR THE HOSTAL PAMPLONA OF THE CITY OF CARIAMANGA, CANTÓN CALVAS, PROVINCE OF LOJA", which allowed to achieve a better development and performance of its activities In their daily work and achieve a greater position in the market of the city of Cariamanga. At present, companies and industries find barriers that do not allow their expansion and growth in the market, this forces to implement strategic objectives in which the importance of carrying out an adequate marketing planning must be analyzed because today the competition and the subsistence in The market focuses on customer satisfaction, hoarding more percentage of them and providing quality services. In this study we considered the corresponding conceptual elements in importance and that constitute the bibliographic basis of marketing topics for the development of this research work. Among the methods and techniques used are the historical, statistical, inductive, deductive, analytical method used to elaborate and develop the objectives of the project. "Techniques such as the interview to the manager, 8 employee surveys and 366 external clients that facilitated obtaining the primary information necessary to clarify the current situation of the Hostel. In the Matrix of external factors, the results obtained from the external analysis of the company were taken, choosing the most representative opportunities and threats. A relative weight was assigned to each of the factors according to the criterion of 0 not important up to 1 very important; The sum of these weights must always be equal to 1. In the present case, a rating was assigned to each factor according to the current state of that factor, analyzing whether or not opportunities are attractive and what harm can be exerted on the threat. Company, multiplied the weight for each factor to obtain a weighted score and added the column of the total score to obtain the weighted total of the hostel, obtaining a total of 2.70; This means that the opportunities are above the threats and can be exploited through strategies that allow and exploit them as much as possible so that the Hostel Pamplona, position in a good place in the market. The Matrix of internal factors determined the strengths and weaknesses of the Hostal Pamplona, which we proceeded to assign values weighted according to the importance of each factor, considering the following criteria; 0, 0 not important to 1.0 very important, the assigned values indicates the relative importance of the factor to make the company successful. Subsequently qualifying values were assigned from one to four to each factor that represents a greater weakness giving a rating of one, a minor weakness giving a rating of two, a lower strength giving a rating of three and a higher strength giving a rating four . The value of each factor was multiplied by its rating to determine a weighted value for each variable. Finally we added the weighted values of each variable, obtaining the total weighted value, which is 2.76 which means that the strengths are above the weaknesses, therefore it is necessary to make improvements to reduce the weaknesses and to have A better use of the strengths, having to be taken into account because it needs that the strengths are increased within the same one. After knowing the internal and external reality of the hostel Pamplona, the strengths and weaknesses, as well as their opportunities and threats, were defined. The strategic objectives were defined, which allowed to initiate the development of the marketing proposal to the hostel, and To define the indispensable guiding framework to correct the deficiencies and to lead to better perspectives of growth and development. Among the strategic objectives, 5 objectives were determined: First: To attract new clients to increase sales by 50% in the Hostel, second; Implement an updated computer system (software) with a database with the objective of providing a quality service to customers and thus become a Leader Hostel in the market, third; Carry out a training plan for the hostel through the SECAP with the objective of overcoming the competition and improving the positioning in the market; Fourth; Carry out an advertising plan to increase by 50% the dissemination of the services offered by the Hostal, fifth; Implementation of an additional cafeteria service at the Hostal Pamplona. The strategic plan to be implemented amounts to a total of US $ 7301.00, since executing the present marketing plan, will allow the hostel to achieve a better development and positioning in the market of the city of Cariamanga in that it refers To lodging, improving their clientele. Finally, we present the conclusions and recommendations that have been determined, after the study carried out through the marketing planning process, the same that will be put to the consideration of the manager of the hostel for its subsequent execution of the Marketing Plan for the Hostal Pamplona in the city Of Cariamanga.